2022
DOI: 10.1007/s43452-022-00552-z
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcements in 3D printing concrete structures

Abstract: 3D printing of concrete structures has had a strong development in recent years, enhanced by the advantages it presents over traditional construction.However, it currently still has some limitations. One of those limitations is to incorporate the reinforcements into the automated 3D printing process. The objective of this work is to present a review of the methods that have been used so far to reinforce the structures. The different methods used will be presented focusing on the reinforcement by the use of fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Various types of reinforcements have been employed for 3D printing, such as steel micro cable, U-nail, mesh, vertical insertion of bars, and short fibers, among others. Studies have reported positive results after the insertion of reinforcement, demonstrating significant improvements in compressive strength (Kazadi et al 2022;Mechtcherine et al 2019;Alonso-Canon et al 2022;Nodehi et al 2022;Lim et al 2020). Examples of such studies and the observed strength changes after the insertion of reinforcement are discussed below.…”
Section: Reinforcement In 3d Printed Concretementioning
confidence: 99%
“…Various types of reinforcements have been employed for 3D printing, such as steel micro cable, U-nail, mesh, vertical insertion of bars, and short fibers, among others. Studies have reported positive results after the insertion of reinforcement, demonstrating significant improvements in compressive strength (Kazadi et al 2022;Mechtcherine et al 2019;Alonso-Canon et al 2022;Nodehi et al 2022;Lim et al 2020). Examples of such studies and the observed strength changes after the insertion of reinforcement are discussed below.…”
Section: Reinforcement In 3d Printed Concretementioning
confidence: 99%
“…As it has been discussed in the numerical simulations sections (2.3 and 3.2), the ARs could stand the forces exerted by the water without the need of reinforcement bars. The use of fibers to reduce the section of the ARs was also discarded, because the maximum increment on flexural strength that fibers could supply would not be more than % [40], which is considered still quite low to be contemplated as a substitute of rebars. A.I.…”
Section: Artificial Reef Designmentioning
confidence: 99%
“…In particular, many works related to 3D printing of elements or entire buildings made of concrete and reinforced concrete should be noted here [ 6 , 7 , 8 ]. The authors develop new technologies for printing concrete objects, allowing for the creation of complex shapes of concrete surfaces, which are characterized by the good print quality and geometric accuracy [ 9 , 10 ]. In recent years, some studies have been conducted on the modal properties of structures made in 3D printing technology.…”
Section: Introductionmentioning
confidence: 99%